Fracture Epidemiology in Professional Baseball From 2011 to 2017. Issue 8 (14th August 2020) - Rubenstein, William J.; Allahabadi, Sachin; Curriero, Frank; Feeley, Brian T.; Lansdown, Drew A.
Background: Fractures are a significant cause of missed time in Major League Baseball (MLB) and Minor League Baseball (MiLB). MLB and the MLB Players Association recently instituted rule changes to limit collisions at home plate and second base. Purpose: To evaluate the epidemiologic characteristics of fractures in professional baseball and to assess the change in acute fracture incidence secondary to traumatic collisions at home plate and second base after the recently instituted rule changes. Study Design: Descriptive epidemiology study. Methods: The MLB Health and Injury Tracking System (HITS) database was used to access injury information on MLB and MiLB players to analyze fracture data from 2011 to 2017. Injuries were included if the primary diagnosis was classified as a fracture in the HITS system in its International Classification of Diseases, Ninth Revision, codes; injuries were excluded if they were not work related, if they occurred in the offseason, or if they were sustained by a nonplayer. The proportion of fractures occurring due to contact with the ground or another person in the relevant area of the field—home plate or second base—in the years before rule implementation was compared with the years after. Results: A total of 1798 fractures were identified: 342 among MLB players and 1456 among MiLB players. Mean time missed per fracture was 56.6 ± 48.4 days, with significantly less time missed in MLB (46.8 ± 47.7 days) compared with MiLB (59.0 ± 48.3 days) ( P < .0001). A 1-way analysis of variance with post hoc Bonferroni correction demonstrated that starting pitchers missed significantly more time due to fractures per injury than all other position groups ( P < .0001). Acute fractures due to contact with the ground or with another athlete were significantly decreased after rule implementation at home plate in 2014 (22 [3.0%] vs 14 [1.3%]; P = .015) and at second base in 2016 (90 [7.0%] vs 23 [4.5%]; P = .045). Conclusion: The recently instituted rule changes to reduce collisions between players at home plate and at second base are associated with reductions in the proportion of acute fractures in those areas on the field.